PENGGUNAAN COMPUTER GENERATED IMAGE PADA VISUAL EFFECT - Paramita Hapsari, S.Ds, M.Ds, Paramita Hapsari, S.Ds, M.Ds (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2022)
In this day and age, for example, the diversion universe, especially in movies, is highly rewarding for action. Various types of films appear and are very interesting to watch. In today's advanced age of broadcast communications, innovation is very persuasive. For the most part in the assembly of different films. Ranging from animated films to fiction films. Therefore, the use of interactive media innovation Computer Generated Imagery (CGI) is needed, to make a film so that the film becomes alive and visible. In shooting Transformers the PC part creates symbolism using this innovation, considering the impact of a vehicle turning into a robot is beyond the reach of the possibility of using manual strategies, eg clothing set per movie set. Therefore, Computer Generated Imagery (CGI) is used for this innovation. In the first environment, it only takes a room with basic animation and then it will be handled into a computer with very high programming specifications. Starting from the impact of traveling to the moon, the fall of meteors, changes in shape and the impact of using CGI, until generally the results will not be good. Furthermore, CGI innovation is not only used in making Transformers films, but also in making films to make them look very charming and cool.